2016
DOI: 10.1002/clen.201500946
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Impact of Organic Fertilization and Seasonal Variations on Enzymes and Microbial Indices Under Rice–Wheat Rotation

Abstract: The impact of organic fertilization (OF) and seasonal variation on microbial indices was compared with chemical fertilization (CF) and integrated nutrient management (INM) practices under rice–wheat sequence. The field experiments conducted from 2011 to 2013, adopting a split‐plot design, showed that CF practices decreased the soil pH, microbial biomass carbon, and CO2 metabolic quotient but increased the percentage of microbial biomass C to soil organic carbon. Organic fertilization though enhanced the soil o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…). Others have also reported enhanced soil biochemical activity in a single growing season ( Arancon et al, ; Dinesh et al., ; Lazcano et al, ; Gaind et al, ) in response to short‐term incorporation of organic manures and biofertilizers. This indicates that instantaneous increases in soil enzyme activities were associated with a rapid increase of organic substrates required for microbial metabolism.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…). Others have also reported enhanced soil biochemical activity in a single growing season ( Arancon et al, ; Dinesh et al., ; Lazcano et al, ; Gaind et al, ) in response to short‐term incorporation of organic manures and biofertilizers. This indicates that instantaneous increases in soil enzyme activities were associated with a rapid increase of organic substrates required for microbial metabolism.…”
Section: Resultsmentioning
confidence: 97%
“…As observed in other studies, long‐term application of organic amendments has also exerted a considerable influence on the activities of soil enzymes in our study, in which enzyme activities were 28 to 42% higher (Tab. ) in organic systems than in their conventional counterparts ( Singh et al, ; Gaind et al, ; García‐Orenes et al, ). Plenty of microbial substrates (C and nutrients) in composts can facilitate microbial population build up ( Witter and Kanal , ) and further stimulate them to produce enzymes responsible for the conversion of unavailable to an available form of nutrients ( Yadav et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study indicated that agricultural intensifications could alter the expressions of soil biochemical indicators (e.g., enzyme activity) quicker than soil microbial diversity indicators (Pérez-Brandán et al, 2016 ). To that end, soil enzyme activities are often used as effective indicators for assessing the environmental consequences of applications of agricultural chemicals for soil nutrition (Gaind and Singh, 2016 ; Sihi et al, 2017 ) and xenobiotic pesticides (Sahoo et al, 2016 ; Mahapatra et al, 2017 ). One can also evaluate the ecological consequences (e.g., soil carbon loss) of land use management intensities, along with a wide spatial gradient of edaphic factors, using microbial ecophysiological traits, including growth efficiency, qCO 2 , and indicator proteins (Malik et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…This was in accordance with who reported higher DHA values in soils amended with compost and humic acid as compared to soil fertilized with chemical fertilizers. Chemical fertilizers may also promote the growth of microbial communities as compared to control by countering the limitation of mineral nutrients (Gaind and Singh 2016).…”
Section: Dehydrogenase Enzymementioning
confidence: 99%